KONTROL LAMPU DENGAN MENGGUNAKAN MODUL NODEMCUESP8266 V.3 BERBASIS TELEGRAM BOT - Rizaldi, Muhamamad Jimi; Radwitya, Erick; Risman, Jaya (Injection: Indonesian Journal of Vocational Mechanical Engineering, 2022)
The creation of this final project project can turn on and off the lights using the internet network. The internet is an extensive network that can be accessed by anyone and anywhere. In this Final Project, the lamp control application used is an application that is very common in society, namely telegram. By using the telegram bot we can connect with the module used for the light controller. With this remote light control tool, we can turn the lights off or on even from abroad. Only by using our smartphones, we can do this under any circumstances. We can also check the status of the lamp we control whether it is on or is in a dead state.The results of the design of lamp control via Telegram using components in the form of lights, relays, NodeMCU ESP8266 modules. After programming the NodeMCU ESP8266 module, in the design of this tool, the following components were obtained, namely 20 watts 4 lamps, 4 channel 1 relays, ESP8266 NodeMCU Modules with a maximum input of 12 volts.